No Shipping Fees or Free Shipping? Impact of Temporal Proximity on the Relative Effectiveness of Promotional Framing - Kulkarni, Atul A. (Journal of Promotion Management, 2020)
In this research, we find that the relative effectiveness of framing a shipping promotion as “no shipping fees” versus “free shipping” may depend on temporal proximity of the promotional offer. Our findings suggest that when the promotion is on offer in immediate future, framing it as no shipping fees is relatively more effective. In contrast, when the promotion is on offer in relatively distant future, framing is as free shipping is relatively more effective. Our findings also suggest that these differences in the relative effectiveness of the two framing types may be subject to the degree of elaboration. The differences may manifest when consumers process promotional information cursorily but may dissipate when consumers elaborate more. When primed to process information cursorily, participants in our studies (Studies 1 and 2) reported higher offer evaluations and purchase intentions when (i) an ongoing promotion was framed as no shipping fees or (ii) a promotion available in the future was framed as free shipping. These effects dissipated when either the participants were primed to elaborate more (Study 3) or when the temporal aspect was eliminated (Study 4).
Keywords: dept.mrk; evaluation; framing; free shipping; peer-reviewed; promotions; temporal distance

Shopper Search in Response to Conditional Promotions: A Function of Basket Sizes and Incentive Types - Kulkarni, Atul; Yuan, Hong (Psychology and Marketing, 2025)
Keywords: Advertising; Business; Computer science; Consumer Attitudes; Consumer Behavior; Economics; Function (biology); Incentive; Incentives; Mathematics; Microeconomics; Shopping; dept.mrk; peer-reviewed

Construal-level Mindsets Enhance Behavioral Persistence in Response to Incentive Valence - Kulkarni, Atul A.; Yuan, Hong (Journal of Behavioral Decision Making, 2017)
In this research, we find that incentive valence and construal-level mindsets can interact to influence behavioral persistence on challenging tasks. An abstract mindset improves persistence in response to positively framed incentives whereas a concrete mindset improves persistence in response to negatively framed incentives. This interaction effect can be observed even when the cues inducing construal-level mindsets are not related to the incentives or the incentivized tasks. Participants in our studies were either positively or negatively incentivized to solve a set of difficult anagrams, and were primed with an abstract or a concrete mindset using spatial (Study 1) and social (Study 2) cues. The participants persisted longer in response to the positively framed incentive when primed with spatially or socially remote cues. In contrast, for the negatively framed incentive, participants persisted longer when primed with spatially or socially proximal cues. Copyright © 2017 John Wiley & Sons, Ltd.
Keywords: construal-level; dept.mrk; incentive valence; mindset; persistence

Induction of Construal-Level Mindset via Experience of Surprise: An Abstract: Proceedings of the 2018 Academy of Marketing Science (AMS) Annual Conference | Request PDF - Kulkarni, Atul A.; Vanhamme, Joelle (2018)
Request PDF | Induction of Construal-Level Mindset via Experience of Surprise: An Abstract: Proceedings of the 2018 Academy of Marketing Science (AMS) Annual Conference | An experience of surprise is often an outcome of disconfirmation of expectations and can be associated with positive or negative affect depending... | Find, read and cite all the research you need on ResearchGate
Keywords: dept.mrk

Boomerang effect of incentive reminders during shopping trips - Kulkarni, Atul; Wang, Xin Cindy; Yuan, Hong (Journal of Consumer Marketing, 2019)
Purpose This paper aims to examine the unintended negative effect of incentivizing shoppers to make unplanned purchases through incentive reminders during shopping trips. Design/methodology/approach Two experimental studies with between-subject designs were conducted to examine the effect of incentive reminders and related factors on abandonment intention. Findings When the search for unplanned purchases needed to reach promotional threshold fails, shoppers’ propensity to abandon a transaction increases if they are reminded of an incentive during their shopping trip. When the size of the planned purchases is relatively larger than the incentivized unplanned purchases, abandonment propensity is higher in response to reward type incentives, whereas when the size of the planned purchases is relatively smaller than the incentivized unplanned purchases, abandonment propensity is higher in response to avoidance type incentives. Research limitations/implications This research intersects and integrates several research domains, specifically transaction abandonment, promotional reactance, unplanned purchases and promotion framing. Practical implications Findings from this research help managers understand the possible negative consequences of incentive reminders and offer suggestions for decreasing shopper propensities to abandon transactions in response to incentive reminders aimed at increasing transaction sizes. Originality/value This is the first study to highlight (i) the possible effect of incentive reminders on transaction abandonment; (ii) the influence of the size of unplanned purchases and incentive types on abandonment; and (iii) the underlying roles of perceived value of planned purchases and fairness perceptions in abandonment.
Keywords: Incentive reminders; Promotional reactance; Transaction abandonment; dept.mrk; peer-reviewed